Compositional and thermal analysis of RBD palm oil adulterated with lipase-catalyzed interesterified lard - Marikkar, Mohammed Nazrim; Lai, O.M.; Ghazali, H.M.; Che Man, Y.B. (Elsevier, 2002)
A study was conducted to determine the presence of enzymatically randomized lard (ERLD) as adulterant in RBD palm oil using three different analytical techniques namely gas liquid chromatography (GLC), reversed phase high performance liquid chromatography (RP-HPLC) and differential scanning calorimetry (DSC). Lard extracted from the adipose tissues of pig was enzymatically interesterified using nonspecific lipase from Pseudomonas sp. Compositional and thermal characteristics of ERLD was compared with those of genuine lard (GLD). RBD palm oil samples adulterated separately with various levels of GLD and ERLD were analyzed using GLC, HPLC and DSC. Both GLC and HPLC did not show any characteristic adulteration peaks that enable RBD palm oil adulterated with either GLD or ERLD to be distinctly identified from those adulterated with chicken fat (CF), whereas DSC provided a better means of detection of lard with the detection limit of 1%.